عہد نبوی ﷺ میں خواتین کا نظام تعلیم و تربیت (تجزیاتی مطالعہ ): The System of Education and Training for Women in the Prophetic Era (An Analytical Study) (Al-Aasar, 2025)
This study delves into the system of education and training for women during the Prophetic Era. It examines how educational opportunities were systematically provided for women in that blessed period, with a special focus on their religious, ethical, social, and even practical upbringing. We will analyze the educational methodologies of that era, which included teaching arrangements for women in mosques, homes, and specialized academic gatherings. The aim of this study is to elucidate how Prophet Muhammad (PBUH) declared the pursuit of knowledge obligatory for both men and women, encouraging women not only towards spiritual purity but also to become active members of society. This research sheds light on how these women, foremost among them the Mothers of the Believers and the female Companions, acquired knowledge and played pivotal roles in shaping Islamic society, narrating Hadith, providing jurisprudential guidance, and contributing to various social services. This analytical study also offers guidance for contemporary Muslim societies to empower women in all walks of life by following the comprehensive educational model established by the Prophet (PBUH).